Dynamic Changes of the Fungal Microbiome in Alcohol Use Disorder - Hartmann, Phillipp; Lang, Sonja; Zeng, Suling; Duan, Yi; Zhang, Xinlian; Wang, Yanhan; Bondareva, Marina; Kruglov, Andrey; Fouts, Derrick E.; Stärkel, Peter; Schnabl, Bernd (Frontiers in physiology, 2021)
Alcohol-associated liver disease (ALD) is an important cause of morbidity and mortality worldwide. The intestinal microbiota is involved in the development and progression of ALD; however, little is known about commensal fungi therein. We studied the dynamic changes of the intestinal fungal microbiome, or mycobiome, in 66 patients with alcohol use disorder (AUD) and after 2 weeks of alcohol abstinence using internal transcribed spacer 2 (ITS2) amplicon sequencing of fecal samples. Patients with AUD had significantly increased abundance of the genera , , , , and , and of the species and compared with control subjects. Significantly improved liver health markers caspase-cleaved and intact cytokeratin 18 (CK18-M65) levels and controlled attenuation parameter (CAP) in AUD patients after 2 weeks of alcohol abstinence were associated with significantly lower abundance of the genera , , , , , and the species and . This was mirrored by significantly higher specific anti- immunoglobulin G (IgG) and M (IgM) serum levels in AUD patients in relation to control participants, and significantly decreased anti- IgG levels in AUD subjects after 2 weeks of abstinence. The intestinal abundance of the genus was significantly higher in AUD subjects with progressive liver disease compared with non-progressive liver disease. In conclusion, improved liver health in AUD patients after alcohol abstinence was associated with lower intestinal abundances of and , and lower serum anti- IgG levels. Intestinal fungi might serve as a therapeutic target to improve the outcome of patients in ALD.